2014
DOI: 10.1016/j.canlet.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200, a new star miRNA in human cancer

Abstract: MicroRNAs (miRNAs) are a set of non-coding small RNA molecules in control of gene expression at posttranscriptional/translational level. They not only play crucial roles in normal developmental progress, but also are commonly dysregulated in human diseases, including cancer. MiR-200 is a family of tumor suppressor miRNAs consisting of five members, which are significantly involved in inhibition of epithelial-to-mesenchymal transition (EMT), repression of cancer stem cells (CSCs) self-renewal and differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
265
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(279 citation statements)
references
References 107 publications
5
265
0
7
Order By: Relevance
“…Bioinformatics search 12,13 for miRNA-responsive elements in the FUS 3 0 -UTR indicated that among the identified 3 0 -UTR mutations 7 , two patients carried the G48A substitution (in one case of inherited type), which localizes to a predicted binding site for miR-141 and miR-200a. These two miRNAs share the same seed sequence and belong to the same miRNA family 14 The members of this family are of particular interest for human health and disease, because they have been shown to be downregulated during tumour progression and to act as key regulators of epithelial-to-mesenchymal transition 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatics search 12,13 for miRNA-responsive elements in the FUS 3 0 -UTR indicated that among the identified 3 0 -UTR mutations 7 , two patients carried the G48A substitution (in one case of inherited type), which localizes to a predicted binding site for miR-141 and miR-200a. These two miRNAs share the same seed sequence and belong to the same miRNA family 14 The members of this family are of particular interest for human health and disease, because they have been shown to be downregulated during tumour progression and to act as key regulators of epithelial-to-mesenchymal transition 15 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not clear how TSHR suppresses EMT. Previous studies have demonstrated that microRNA (miRNA/miR) serves an important role in EMT; for example, miR-146b-5p induces EMT through the regulation of Wnt/β-catenin signaling (19,20) and the miR-200 family inhibits polycomb complex protein BMI1, and zinc finger E-box-binding homeobox 1 and 2, to suppress EMT (21)(22)(23). Further studies are required to demonstrate whether TSHR regulates EMT through miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, activation of protein kinase C and ERK by sublytic MAC doses (48) also sets into motion mortalin-dependent release of MAC from cells attacked by complement (16). miR-200 family members are major regulators of epithelialmesenchymal transition (49) and are believed to be generally involved in cancer progression, metastasis, and chemoresistance (50). Downregulation of miR-200 family members was proposed to be essential for progression and invasiveness of breast (51,52) and ovarian cancer, and its high expression is associated with improved survival of ovarian (53) and pancreatic cancer patients (54).…”
Section: Discussionmentioning
confidence: 99%